Guidance of Prisoners in Penitentiary - Santoso Budi NU; Doris Rahmat (Wacana Hukum, 2020)
The prison system that emphasizes the elements of revenge and detention accompanied by a "prison house" institution is gradually seen as a system and means that are not in line with the concept of rehabilitation and social reintegration, so that prisoners are aware of their mistakes, In the correctional system, prisoners, children Penitentiary students have the right to get spiritual and physical guidance, and their rights are guaranteed to carry out worship, deal with outsiders, both families and other parties, and obtain information both print and electronic media obtain proper education and so on. Formulation of the problem How guidance prisoners. Objective To find out the guiding of prisoners in a penitentiary. The method used in this research is a sociological juridical approach, which is a research approach that looks at and examines the laws and regulations related to the problem and connects the reality that occurs in the field. That the implementation of inmate training is carried out based on a penal system which is a guidance to the prisoners' personalities carried out by a coaching program with forms of guidance in the form of religious education, general education, skills courses, recreation, sports, arts and work training.